Proceedings of the 2nd ACM SIGHIT International Health Informatics Symposium 2012
DOI: 10.1145/2110363.2110368
|View full text |Cite
|
Sign up to set email alerts
|

Digital-pheromone based difficulty adaptation in post-stroke therapeutic games

Abstract: In this paper, we propose a dynamic difficulty adaptation approach for serious games dedicated to upper-limb rehabilitation after stroke. The proposed approach aims to provide a personalized rehabilitation session in which the training intensity and challenges can be adapted to patient's abilities and training needs. The objective is to increase the rehabilitation volume by getting the patient engaged in the therapy session. This approach has been implemented and tested through a point and click game. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…The results of these user studies suggest that it is important to individually adapt rehabilitation measures to user preferences for therapy to be successful. In this context, Gouaïch et al 46 present a first approach toward dynamic difficulty adaptation in games for older adults who had a stroke. Overall, the authors concluded that the augmentation of stroke rehabilitation with information technology represents a valuable design opportunity.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The results of these user studies suggest that it is important to individually adapt rehabilitation measures to user preferences for therapy to be successful. In this context, Gouaïch et al 46 present a first approach toward dynamic difficulty adaptation in games for older adults who had a stroke. Overall, the authors concluded that the augmentation of stroke rehabilitation with information technology represents a valuable design opportunity.…”
Section: Rehabilitationmentioning
confidence: 99%
“…This can be achieved through person-centric design, where various aspects of the game adapt to individual players [34]. This adaptation should occur dynamically, including elements, such as real-time difficulty adjustment, that are based on increasing user proficiency [35,36]. To measure the effectiveness of a game's adaptation, Flow Theory [37] is often used, wherein the user's engagement is mapped as a relationship between user skill and game difficulty.…”
Section: Serious Gamesmentioning
confidence: 99%
“…Embora exija mais tempo de desenvolvimento, a abordagem adaptativa em tempo real com algoritmos pode proporcionar melhores resultados na motivação do paciente, pois seria fácil identificar as suas dificuldades e modificar o jogo para torná-lo mais fácil de jogar antes que possa causar frustração, da mesma forma, o algoritmo poderia aumentar gradualmente a dificuldade, por exemplo, quando o jogo é muito fácil para o paciente, de modo que ele se sinta desafiado e não se canse da atividade (Gouaich, Hocine, Dokkum & Mottet, 2012).…”
Section: Tecnologias De Apoio No Processo De Reabilitaçãounclassified